PENYULUHAN KESEHATAN TENTANG PENCEGAHAN DISMENORE DI MTSN 1 KOTA LHOKSEUMAWE - Meutia Zuhra; Inong Sri Rahayu; Abdul Gani (LPPM Universitas Al Muslim, 2022)
. Dysmenorrhea is pain in the lower abdomen, sometimes radiating to the waist and thighs. This pain occurs before or during menstruation and lasts for a few hours to several days. Almost all women experience discomfort in the lower abdomen during menstruation. Lack of knowledge among female students about reproductive health includes menstrual disorders. This is because the students do not have any knowledge about it. In addition, although they could freely access information on reproductive health, it does not come from experts, so they may get invalid information. Schools or other health parties are also very minimal in providing counseling or training, especially about reproductive health. The purpose of this community service activity is to provide knowledge and understanding of overcoming menstrual disorders, namely dysmenorrhea in adolescent girls at MTsN 1 Lhokseumawe City and to motivate teenagers to be creative and productive during menstruation, in order to become creative and productive teenagers. The method used in this community service was counseling with three stages of activities including the preparation, implementation and evaluation stages. The result of this activity was an increase in the knowledge and attitudes of adolescents towards the prevention of dysmenorrhea, the activity was carried out smoothly with good support and 100% attendance. It is hoped that partners will continue health education activities and are scheduled regularly.